Homo mobilis: Some observations on the characteristics of the Kura-Araxes cultural complex - Avetisyan, Pavel (ARAMAZD: Armenian Journal of Near Eastern Studies, 2022)
The terms ‘enclosed nomadism’ and ‘dimorphic structure’ which are used to describe the relationship between the Near Eastern mobile pastoralists living in the same habitat and sedentary agricultural communities, are fully applicable also for the description of the socio-cultural landscape of the second half of the 4th millennium BC in Armenia. Archaeological data accumulated year by year provide an opportunity to consider in more detail the relationship between the agricultural and specialized mobile pastoral groups in the region. From this point of view, important data are provided by the settlement of Godedzor, which represents the final stage of the Chalcolithic period, as well as by the clusters with materials of the early stage of the Kura-Araxes cultural complex (Talin, Avan, Tsaghkalanj), which are not associated with settlements.